Development and Feasibility of a Cell Phone–Based Transitional Intervention for Women Prisoners With Comorbid Substance Use and Depression. (September 2015) - Johnson, Jennifer E.; Williams, Collette; Zlotnick, Caron
This article describes the development and feasibility testing of a cell phone–based intervention (Sober Network IPT) among 22 women with comorbid substance use and depressive disorders transitioning from prison to surrounding communities. Feasibility/acceptability measures included phone logs, exit interviews, and pre–post measures of substance use, and depressive symptoms up to 9 months post-release. Results indicated that phone-based transitional treatment is feasible and acceptable. Participants valued the opportunity to maintain contact with familiar prison treatment providers by phone after release, and used the cell phones for help with service linkage, support, and crisis management. We describe relational and practical lessons learned.